Recovering valuable metals from spent hydrodesulfurization catalysts by co-leaching, dissociation, and stepwise precipitation. Issue 2 (April 2023) - Chen, Bingxu; Du, Hao; Guo, Yuning; Wang, Shaona; Peng, Jianping; Zhang, Yi; Li, Lanjie; Xu, Congmei
Abstract: This study discusses an effective and environmentally friendly process for recovering vanadium, nickel, and molybdenum from spent hydrodesulfurization catalysts using an (NH4 )2 SO4 -H2 O2 solution. The leaching efficiencies of vanadium, nickel, and molybdenum were close to 92 %, 97 %, and 84 % under optimum operating conditions (H2 O2 concentration 1.5 mol/L, pH 3.5, temperature 55 °C, liquid to solid mass ratio 15/1, and time 180 min). The presence of MoV9 O28 5- changed the solubility of NH4 VO3 in the (NH4 )2 SO4 solution. Therefore, it is difficult to separate NH4 VO3 using the traditional cooling crystallization method. MoV9 O28 5- was pre-oxidized by adding H2 O2 to the leachate to separate vanadium and molybdenum from the (NH4 )2 SO4 solution. After oxidation, MoV9 O28 5- was converted to MoO3 (O2 ) 2- and V10 O28 6-, and precipitated from the leachate as H2 MoO5 ·H2 O and (NH4 )2 V6 O16 · 1.5 H2 O. Finally, NH4 VO3 and (NH4 )6 Mo7 O24 · 4 H2 O with purities of 99.59 % and 99.04 %, respectively, were obtained via sequential precipitation. In addition, after separating vanadium and molybdenum, nickel was recovered from the leachate in the form of Ni(NH4 )2 (SO4 )2 · 12 H2 O using cooling crystallization, with a purity of 99.88 %. Thus, the leaching solution could be effectively recycled. Graphical Abstract: ga1 Highlights: Leaching of aluminum can be controlled by regulating the concentration of (NH4 )2 SO4 and pH value of the solution. The high NH4 VO3 solubility in concentrated ammonium sulfate solution is determined by the MoV9 O28 5- structure. Separation of vanadium, nickel, molybdenum, and aluminum can be achieved by oxidative modulation of the solution structure. The proposed closed-loop process eliminates the introduction of other ions and avoids wastewater generation.